Psychology from an Islamic perspective: a guide to teaching and learning - Noor, Noraini M. (IIUM Press, 2009)
Current psychological theories of man reject a metaphysical order of reality and ignore the transcendental dimension of the human constitution, contrary to the Islamic perspective. As such, there is an urgent need for a teaching programme that gives students the required exposure to enable them to take account of the differences in the two paradigms. This guide presents the Islamic view of man and compares and contrasts this view with those of contemporary psychology. It then reformulates the latter so that they fit into the Islamic mould.